DAMPAK ECONOMIC FREEDOM TERHADAP PERTUMBUHAN EKONOMI NEGARA ASIA - Suparyati, Agustina; Fadilah, Nurul (Jurnal Ekonomi & Studi Pembangunan, 2015)
Abstract: This study aimed to examine the effect of variable FDI, exchange rate and economic freedom and its constituent components in influencing economic growth in Asian countries, which are grouped into two groups: the group of developing countries that consists of 7 countries including Indonesia, Thailand, Malaysia, Vietnam, Laos, Cambodia and the Philippines, while for developed countries group consisting of four countries, namely Japan, South Korea, China and Singapore in the period 2001-2012. Analysis method used is the analysis of panel data. Variable FDI and exchange rate as a classical variable proved significantly positive effect on economic growth in both developed and developing countries . Components of economic freedom are shown to have a significant effect on economic growth in developing countries in Asia is a variable property rights, business freedom, trade freedom and freedom fmancial While the components of economic freedom are shown to have a significant effect on economic growth in developed countries in Asia is a variable property right, freedom froin corruption, government spendin, monetary freedom, business freedom, and freedom fmancial .In developing countries the best model is the model of the pillars of an open market in which there is a component Trade Freedom, Investment Freedom and the Financial Freedom.Â Abstrak: Studi ini bertujuan untuk melihat pengaruh variabel FDI, nilai tukar serta economic freedom dan komponen penyusunnya dalam mempengaruhi pertumbuhan ekonomi di negara-negara Asia yang dikelompokkan menjadi 2 kelompok yaitu kelompok negara berkembang yang terdiri dari 7 negara antara lain Indonesia, Thailand, Malaysia, Vietnam, Laos, Kamboja dan Filipina,sedangkan untuk kelompok negara maju yang terdiri dari 4 negara yaitu Jepang, Korea Selatan, Cina dan Singapura dalam periode 2001-2012. Metode analisis yang digunakan adalah analisis data panel. Variabel FDI dan nilai tukar sebagai variabel klasik terbukti secara nyata berpengaruh positif terhadap pertumbuhan ekonomi baik di negara maju maupun berkembang. Komponen penyusun economic freedom yang terbukti berpengaruh signifikan terhadap pertumbuhan ekonomi di negara sedang berkembang di Asia adalah variabel property right, business freedom, trade freedom dan fmancial freedom Sedangkan komponen penyusun economic freedom yang terbukti berpengaruh signifikan terhadap pertumbuhan ekonomi di negara maju di Asia adalah variabel property righl, freedom froin corruption, government spending, monetary freedom, business freedom, dan fmancial freedom. Di negara sedang berkembang model terbaik adalah model pilar open market yang di dalamnya terdapat komponen Kebebasan Perdagangan, Kebebasan Investasi dan Kebebasan Finansial.